IMPLEMENTATION OF VARIETAL PRODUCTIVITY OF FRAGARIA ANANASSA DUCH UNDER THE INFLUENCE OF DOMESTIC PREPARATIONS SUCH AS PPE, BIOFOOD, MICRONUTRIENTS - Rozhko І.С.; Rozhko І.М. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
The article presents the results of comparative evaluation of the impact of domestic preparations, particularly biological agents: Phytocide-r®, Mycohelp®, Humifrend®, Organic – balance® and microfertilizers and compatible fungicides Strazh and Jackpot. on the foundamental components of productivity and the implementation of varietal productivity of Fragaria ananassa Duch. The study was carried out in the planting of two varieties of strawberries: ‘Florence’ and ‘Elsanta’. There were six variants of each of the studied varieties. The control was without any treatment, with a natural background of varietal field resistance to major fungal diseases: powdery mildew, gray rot and leaf spots. The studied varieties responded differently to the applied preparations. The highest pathogenic deterrent effect on both studied varieties of pineapple strawberries was observed in the variants of using microfertilizer Avangard P Fruit and Berries + fungicide and Phytocide-p®. The plant conditions were excellent – healthy leaves, strong plants, signs of damage of Oidium fragariae Harz. and Ramularia Tulasnei Sacc were absent, and Botrutis cinerea Pers lesions were 2–4 % versus 8–16 % in controls. The ‘Elsanta’ variety responded well to the use of Mycohelp®: signs of Oidium fragariae Harz and Ramularia Tulasnei Sacc were absent, and Botrutis cinerea Pers was 4 % as compared to 16 % in the control. The highest level of varietal productivity was observed in the variants with the use of microfertilizers Avangard P Fruit and Berries + fungicide and Phytocide-p®. In both cases, only compliance with the recommended doses, timing and methods of treatment with certified domestic preparations ensured conducting responsible berry growing, the purpose of which was to obtain a safe vitamin product.